Membership Determination of van den Bergh Open Clusters vdB92, vdB146 (NGC 7129) and vdB150 - Orellana, Rosa Beatriz (2017)
In this paper we study some van den Bergh open clusters combining photometry and astrometry. A model which analyses the proper motion distribution and the stellar density is applied to find the kinematic parameters and stellar membership in the region of the open clusters vdB92, vdB146 (NGC 7129) and vdB150. The astrometric data are obtained from UCAC4 catalogue. The centre coordinates, the components of mean proper motion, the angular diameter and the astrometric members are reported, taking the following values: for vdB92: α=105.97281°±0.13113°, δ=−11.57814°±0.10575°, μαcosδ=−3.46±0.19mas/yr,μδ=1.27±0.19mas/yr, 34´, 60 members; for vdB146: α=325.78423°±0.15297°, δ=66.13575°±0.02907°, μαcosδ=−2.71±0.25mas/yr, μδ=−3.32±0.25mas/yr, 9´, 5 members; and for vdB150: α=332.22519°±0.06074°, δ=73.40232°±0.0.07789°, μαcosδ=3.07±0.90mas/yr, μδ=4.65±0.90mas/yr, 15´, 7 members. The incidence of the proper motion errors in the determination of the cluster parameters and of the stellar membership is analysed and it is found that they do not significantly change. We finally compare the astrometric members with the photometric ones given in the literature.